Factores de riesgo asociados al parto pre término en el hospital nacional Guillermo Almenara Irigoyen de enero a junio del 2010. - Díaz Polo, Lizbeth Estefanía (2019)
Preterm birth occurs between 22 and before 37 weeks. Its etiology is multifactorial and is a major cause of perinatal morbidity and mortality. The objective was to determine the risk factors associated with preterm delivery in pregnant women Guillermo Almenara Irigoyen National Hospital from January to June 2010. We performed a retrospective case - control and descriptive. The case histories of patients and controls were reviewed and recorded in chips and processed with SPSS version 15. The results were 81 patients diagnosed with preterm birth, with statistical significance in the following variables: absence of prenatal care (OR 3.07, P> 0.05), pre-eclampsia (OR 20.86, P <0.001), premature rupture of membranes (OR 4.03, P> 0,005), multiple pregnancy (OR 5.64, P> 0.01), chorioamnionitis (OR 2.02, P> 0.1), place of birth: saw (OR 3.88, P> 0.05) and socioeconomic status (OR12.73, P> 0.05). It was evident that more poor pregnant women with less education have a higher incidence of preterm delivery [1] [2] [3]. That 21% of preterm births was associated with premature rupture of membranes (OR 4.03) data that is within the range of incidence, as Aagaard-Tillery [4] (2005) noted an incidence of premature rupture preterm membrane between 30 and 40% and Fabian (2008) observed 11.67% of premature rupture of membranes [5]. Pregnant women with preeclampsia had a 20 times higher risk of preterm birth present. 34.6% presented with preterm birth pre-eclampsia, of which 42.8% was severe preeclampsia, 25% and 32.14% mild HELLP syndrome; data Salviz similar to that observed in their study in the Cayetano Heredia Hospital, where he found a 30 % of preterm birth in patients with preeclampsia, although it is known that pre-eclampsia affects 3 to 5% of pregnancies, no studies on the incidence of preeclampsia in preterm labor [6]. We conclude that the main risk factor associated with preterm delivery was preeclampsia. Being born in the mountains, belong to socioeconomic status, lack of prenatal care, premature rupture of membranes, coriomanionitis and multiple pregnancy were also significant.